Thoracic load carriage impairs the acute physiological response to hypoxia in healthy males - Daniel A. Baur; Caroline M. Lassalle; Stephanie P. Kurti (Physiological Reports)
Abstract To assess the impact of thoracic load carriage on the physiological response to exercise in hypoxia. Healthy males (n = 12) completed 3 trials consisting of 45 min walking in the following conditions: (1) unloaded normoxia (UN; FIO2:20.93%); (2) unloaded hypoxia (UH; FIO2:~13.0%); and (3) loaded hypoxia (LH; 29.5 kg; FIO2:~13.0%). Intensity was matched for absolute VO2 (2.0 ± 0.2 L·min−1) across conditions and relative VO2 (64.0 ± 2.6 %VO2max) across hypoxic conditions. With LH versus UH, there were increases in breathing frequency (5–11 breaths·min−1; p < 0.05) and decreases in tidal volume (10%–18%; p < 0.05) throughout exercise due to reductions in end inspiratory lung volumes (p < 0.05). Consequently, deadspace (11%–23%; p < 0.05) and minute ventilation (7%–11%; p < 0.05) were increased starting at 20 and 30 min, respectively. In addition, LH increased perceived exertion/dyspnea and induced inspiratory (~12%; p < 0.05 vs. UN) and expiratory (~10%; p < 0.05 vs. pre‐exercise) respiratory muscle fatigue. Expiratory flow limitation was present in 50% of subjects during LH. Cardiac output and muscle oxygenation were maintained during LH despite reduced stroke volume (6%–8%; p < 0.05). Finally, cerebral oxygenated/total hemoglobin were elevated in the LH condition versus UH starting at 15 min (p < 0.05). Thoracic load carriage increases physiological strain and interferes with the compensatory response to hypoxic exposure.